(untitled) (ARQUISUR Revista, 2022)
This article presents and problematizes the field of research within the framework of master’s degrees in architectural design. Its objective is to analyze the research in architectural project attending to the similarities and differences with scientific research —through a comparative analytical method—, with the expectation of understanding and delimiting the particularities of our object of study. Three central questions structure this work: in what way is the field of research in architectural project comparable to the field of scientific research? In the type of research that interests us, how is the research problem constructed? And, finally, what is the role of the project and its techniques in the methodological approach of this type of research? The aspects initially treated at a theoretical level (around the type of knowledge involved in the research in architectural project, the construction of the research problem and the methodological strategies), are contrasted with two case studies —both in the Final Research Plan instance within the framework of the Master’s Degree in Architectural Project at Buenos Aires’ University.